Distribution pattern of different phenotypes of Limnocythere inopinata (an ostracod) from lakes in the Badain Jaran Desert, northern China. (June 2022) - Jiang, Gaolei; Wang, Nai'ang; Zhai, Dayou; Li, Xiangzhong; Mao, Xin; Li, Meng; Liu, Linjing
Highlights: Three ostracod species were identified and related ecological information are reported in the Badain Jaran Desert. The node formation of Limnocythere inopinata is affected by a combination of the salinity and Ca 2+ content of lake water. The relationship between the percentage of noded individuals and salinity of lake water is complex. Abstract: Limnocythere inopinata (Baird, 1843) is a widely distributed ostracod in modern non-marine waters and Quaternary sediments. Based on its morphological variation (the number and position of its nodes), different phenotypes have been identified. However, the factors controlling its morphological variation are currently open to debate, which hinders palaeoecological reconstructions based on this species. In this study, ostracod distribution and hydrochemical analyses of the ambient environment of 21 lakes in the Badain Jaran Desert were carried out. Three ostracod species belonging to two genera are identified as Limnocyhtere inopinata, Cypris cf. granulate and Cypris sp. with the dominant species L. inopinata represented by six phenotypes. The distribution features of these ostracods in the lakes and related ecological information are reported. In addition, the factors controlling the morphological variations of L. inopinata were analysed. Our data indicate that the noded individuals of L. inopinata prefer water with appropriate Ca 2+ content (30–40 mg L −1 ) and low salinities (below 4.60 g L −1 ). The percentage of noded individuals of L. inopinata increases with increasing salinity only within a certain salinity range. Hence, caution should be exercised in reconstructions of palaeosalinity based on the morphological variability of L. inopinata .